Non-destructive orientation mapping of die-attach lead-free solder - Yujiro Hayashi; Hidehiko Kimura (Applied Physics Express)
Thermo-mechanical fatigue poses a serious challenge to the electrical operation of power semiconductor modules, manifested by the degradation of die-attach lead-free solder. So far, orientation microscopy (OM) using electron backscatter diffraction is considered a sensitive approach to characterizing the degradation of solder. However, its destructive character inhibits assessing solder inside the power modules. We propose a non-destructive OM method based on X-ray diffraction and successfully observed the changes in the orientation of the solder caused by thermo-mechanical fatigue. The proposed non-destructive OM method can facilitate the development of reliable power modules by evaluating the degradation of the solder inside the power modules.